2016
DOI: 10.1111/1753-6405.12419
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in remote Aboriginal communities: lessons from Mai Wiru and the Anangu Pitjantjatjara Yankunytjatjara Lands

Abstract: Objective: To examine the impact of efforts to improve nutrition on the Anangu Pitjantjatjara Yankunytjatjara (APY) Lands from 1986, especially in Mai Wiru (good food) stores. Methods: Multiple methods were employed. Literature was searched systematically. In 2012, the store‐turnover method quantified dietary intake of the five APY communities that have a Mai Wiru store. The price of a standard market basket of basic foods, implementation of store nutrition policy requirements and healthy food checklists were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 17 publications
3
54
0
Order By: Relevance
“…A recent review has shown that food insecurity is associated with increased risk of anaemia among women and young children in high and low income countries . Food insecurity and poor diet of Aboriginal and Torres Strait Islander people have been documented in remote settings in Australia …”
Section: Discussionmentioning
confidence: 99%
“…A recent review has shown that food insecurity is associated with increased risk of anaemia among women and young children in high and low income countries . Food insecurity and poor diet of Aboriginal and Torres Strait Islander people have been documented in remote settings in Australia …”
Section: Discussionmentioning
confidence: 99%
“…Lee et al . found that in two remote Aboriginal communities over 26 years there was an increase in the intake of folate from fortified bread, and an increase of niacin and thiamin from fortified breakfast cereals . Brimblecombe et al .…”
Section: Discussionmentioning
confidence: 98%
“…There are challenges for Indigenous communities as the current food supply discourages healthy eating. Indigenous communities are remote and healthy food is relatively expensive compared to unhealthy choices . The price difference of healthy food in remote Northern Territory can be 60% higher than in urban Australia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policies that increase the price differential between healthy and unhealthy diets could further compromise food security in vulnerable groups. 3 However, results also suggest that other factors (such as convenience, availability and marketing of discretionary products) may be as important as price in determining food choice. This confirms policy actions are needed to intervene at multiple points and levels in the food and nutrition system.…”
Section: Amanda Lee the Sax Institute Sydney Australiamentioning
confidence: 96%